Can Catholic Social Thought Help to Alleviate Liturgical Tensions? - Gascoigne, Robert (Irish theological quarterly, 2014)
For Catholic social thought, the liturgy is fundamentally a divine site where the inadequacies of even our noblest ethical strivings are offered in humble hope for God’s Kingdom. Yet the liturgy is also a work of humankind, and deeply affected by tensions between the Church and contemporary secularity, manifested, for example, in the decline in participation in the Eucharist and controversies over translation. Since these tensions stem from social experience, Catholic social thought is called upon to understand them and to offer perspectives which can help to name and clarify the connections within this field of tensions. The aim of this article is to draw on some contemporary insights in liturgical theology and in Catholic social thought, in particular the work of Charles Taylor and José Casanova, that relate to this field of tensions and to explore ways in which they might mutually illuminate each other.